2014
DOI: 10.4111/kju.2014.55.11.703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varicocelectomy on Male Infertility

Abstract: Varicocele is the most common cause of male infertility and is generally correctable or at least improvable by various surgical and radiologic techniques. Therefore, it seems simple and reasonable that varicocele should be treated in infertile men with varicocele. However, the role of varicocele repair for the treatment of subfertile men has been questioned during the past decades. Although varicocele repair can induce improvement of semen quality, the obvious benefit of spontaneous pregnancy has not been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Varicoceles can affect various seminal parameters including sperm production. Most authors agree that surgical therapy of varicoceles is an accepted intervention in the treatment of male factor infertility; microsurgical varicocelectomy is regarded as the gold standard [ 53 ]. When compared to androgen replacement therapy, a study by Cho and Seo [ 53 ] found varicocele repair to be more cost-effective in treating infertility.…”
Section: Varicocelementioning
confidence: 99%
See 1 more Smart Citation
“…Varicoceles can affect various seminal parameters including sperm production. Most authors agree that surgical therapy of varicoceles is an accepted intervention in the treatment of male factor infertility; microsurgical varicocelectomy is regarded as the gold standard [ 53 ]. When compared to androgen replacement therapy, a study by Cho and Seo [ 53 ] found varicocele repair to be more cost-effective in treating infertility.…”
Section: Varicocelementioning
confidence: 99%
“…Most authors agree that surgical therapy of varicoceles is an accepted intervention in the treatment of male factor infertility; microsurgical varicocelectomy is regarded as the gold standard [ 53 ]. When compared to androgen replacement therapy, a study by Cho and Seo [ 53 ] found varicocele repair to be more cost-effective in treating infertility. Pain secondary to varicoceles is estimated to affect 2% to 10% of men, but surgical intervention for relief of pain is controversial [ 50 ].…”
Section: Varicocelementioning
confidence: 99%
“…Like varicocele, it can contribute to infertility as theoretically it produces the same effect on spermatogenesis as varicocele. [ 5 ] Since the unavailability of good literature, the treatment plan and indication of surgery may be similar to varicocele. This is probably the first case in literature where bilateral lymphangiocele presented with male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy regarding varicocelectomy as a surgical treatment for male infertility, but most studies have supported the procedure for men with a clinical varicocele (4)(5)(6). It is suggested that varicocelectomy improves semen quality (7), and subsequent pregnancy rates in 34% of the spouses of treated men (8). Moreover, varicocelectomy is more cost effective than both intrauterine insemination and in vitro fertilization (9).…”
Section: Introductionmentioning
confidence: 99%